2(6x-4)=27

Simple and best practice solution for 2(6x-4)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6x-4)=27 equation:


Simplifying
2(6x + -4) = 27

Reorder the terms:
2(-4 + 6x) = 27
(-4 * 2 + 6x * 2) = 27
(-8 + 12x) = 27

Solving
-8 + 12x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 12x = 27 + 8

Combine like terms: -8 + 8 = 0
0 + 12x = 27 + 8
12x = 27 + 8

Combine like terms: 27 + 8 = 35
12x = 35

Divide each side by '12'.
x = 2.916666667

Simplifying
x = 2.916666667

See similar equations:

| log(x+12)=3 | | 2x-[X+1]=5 | | 60=15d | | cos(x)=-3.8 | | 3x-61= | | X^2-14x+17=-6x+2 | | 4(3x+6)=-38+2 | | -2tk=20 | | 6X+5X+9X=180 | | x-x^2=0.19 | | 8-(2z-9)=8-3z | | X^2+3x-24=4 | | 8x^5-196x^4+153x^3-4096x^2=0 | | 12x+1=11x+16 | | 6x-30=5(3+x) | | (X^2+5)+(x^2+4)= | | 9x-(3x+14)=16 | | 3000=(200+8x)(15-.50x) | | -12x+3+12x= | | B(b+4)=140 | | 25=48-3x | | 2p-3(2-2p)=3(p-4)-24 | | 15ab-12a= | | 6(2m-3)-3m-2m=18+m | | 5x+4=53-2x | | 9(x-4)=54 | | X+131=x+61 | | 2x+3+y=4xb | | 5x^2+41x+4=0 | | x^2+7x+23=-3x-1 | | 5(3w+1)=-7 | | 2(x+3)=5x+16 |

Equations solver categories